The ubiquitous equine - Kaup, Karla M. Parker, author; Dormer, James T., advisor; Orman, Jack L., advisor; Bohren, Lenora, committee member; Lundberg, Thomas R., committee member; Twarogowski, Leroy A., committee member (Colorado State University. Libraries, 1995)
I have been a connoisseur of the American back road for quite some time now. "Rural America" is a subculture that is quiet, yet powerful. As I swallow endless ribbons of asphalt one common sight has captivated me all my life. The ever present horse. Landscapes and even backyards all over the country are speckled with horses. The horse seems to have the uncanny ability to be everywhere at the same time. These animals manifest a sense of freedom for me, yet paradoxically it is the horse who is the captive to man. With this body of work I intend to walk up close to the horse, and take away the barrier of the car window, or the fence, and offer my hand to the muzzle, and look them straight in the eyes. In doing so I wish to explore the emotional content through my visual concerns, of this submissive, yet powerful animal. As an artist, I am fascinated with a visual dialogue, one without sound. Even so, I feel an artwork should satisfy all the senses. An image should trigger a stimulus to taste, smell, and hear. This is why I utilize textures, to stimulate a tactile response from the viewer. Texture also allows for a response to "hear" the artwork. I choose to get close to my subject matter so the viewer might even "smell" the artwork. This dialogue is emphasized from the eyes of an animal, to the viewer. The eyes are truly "windows" to the soul, and this silent sense of communication can often metaphorically be "deafening." The image of the horse has proven to be the subject matter which facilitates my visual concerns. These consist of line variations, depth of value, shape organization, and composition. Composition is important for I wish to "fill" the image with the subject matter so that the viewer might get close to the expressive qualities that are emphasized at this distance. Each of these visual concerns, utilized at once or individually express drama and emotion within the context of subject matter which has often been the victim of banal and sentimental stereotypes. This body of work is executed as intaglio prints. Intaglio, as a medium, has the ability to facilitate a wide vocabulary of mark making which executes my visual concerns. The use of soft ground is utilized to "model" and "pull" my image out of the plate through a series of wiping and textural impressions. Sugar lift creates bold and fluid areas which are etched deeply to produce dramatic darks. Variations of line etch and dry point describe differences in line quality, and the use of mezzotint allows for softer tones of grays. Chine colle is also a technique which I use by adhering different colors of paper to my original printing paper. This gives me the ability to create a broader depth of value. My intention with The Ubiquitous Equine has been to create a unique body of work, from subject matter which is intriguing to me, and from media which I find challenging. I wish to utilize to my advantage the individual "language" that each technique may facilitate. With this visual language I want to convey to the viewer, a different perspective of an animal which is familiar and common to us. I intend to present a viewpoint which is intimate, yet without sentiment. One which expresses my own personal vision, by embracing the broad vocabulary of intaglio.
Zip file contains 18 slides of artist's works.
Keywords: Horses in art; Intaglio printing; Mezzotint engraving